The Dynamics of Political Contestation in the 2024 Banten Gubernational Election: A Study of the Factors Behind the Defeat of Andra Soni – Dimyati in Vote Acquisition in Cilegon City - Najmi Laila; Abdul Ghofur (UNIVERSITAS PAKUAN, 2026)
Local elections (Pilkada), as a primary instrument of local democracy, play a crucial role in determining the direction of regional leadership. However, in practice, they often reveal a gap between theoretical assumptions of rational voter behavior and the realities on the ground, which are shaped by social, cultural, and psychological factors. This gap is evident in the defeat of the Andra Soni - Dimyati pair in Cilegon City during the 2024 Banten gubernatorial election, despite their overall victory at the provincial level, indicating variations in voter behavior across regions that have not been widely examined in specific contexts. This study aims to identify and analyze the factors influencing this defeat at the local level. The research employs a qualitative approach, with data collected through interviews, documentation, and literature review, and analyzed using voter behavior theory. The findings reveal that the defeat was influenced by strong party identification, the dominance of local political networks, the influence of informal leaders, suboptimal grassroots campaign strategies, and limitations in penetrating deeply rooted voter loyalty. These findings indicate that voter behavior is not entirely rational, but is shaped by emotional attachments and local socio-political structures. Therefore, this study underscores the importance of sustained political strategies, strengthening local networks, and adopting context-sensitive campaign approaches in addressing the dynamics of politics at the regional level.